Comparative Study of Perceptions of Pregnant Women with Chronic Energy Deficiency (CED) on the Fulfilment of Nutrition in the Prevention of Stunting in Semarang City - Rezkillah, Albrina Roza; Surjoputro, Antono; Sriatmi, Ayun (Indonesian Journal of Global Health Research, 2024)
The development of human resources (HR) is strongly influenced by nutritional factors. The impact of malnutrition on pregnant women leads to low birth weight babies (LBW), malnutrition in toddlers and even stunting. This study aims to determine whether there are differences in the perceptions of pregnant women with chronic energy deficiency on nutritional fulfilment in stunting prevention based on stunting cases in Semarang City. This type of research is quantitative research with analytical observational research using a comparative study approach. The data collection method in this study was interview using a questionnaire that has been prepared by the researcher based on the Health Belief Model theory. The sample in this study were pregnant women with Chronic Energy Deficiency (CED) who were in the health centre with the highest stunting cases and the health centre with the lowest stunting cases, a sample of 50 respondents was taken for each health centre with stunting cases using total sampling. Data were collected by meeting pregnant women with Chronic Energy Deficiency through pregnant women's classes and door to door accompanied by health workers. Based on the results of the analysis, the data were not normally distributed so the data analysis used the Mann-Whitney u test and the significance level (p = 0.05) The results showed that there were differences in the perceived barrier to action of pregnant women with Chronic Energy Deficiency (CED) on the fulfilment of nutrition in preventing stunting based on differences in stunting cases namely (p value 0.033), then other variables did not show differences.